2022
DOI: 10.5851/kosfa.2022.e10
|View full text |Cite
|
Sign up to set email alerts
|

Application of Edible Insects as Novel Protein Sources and Strategies for Improving Their Processing

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box belowArticle Type Mini-review Article TitleApplication of edible insects as novel protein sources and strategies for improving their processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 69 publications
(166 reference statements)
0
14
0
3
Order By: Relevance
“…The amino acid profiles of dried H. illucens pre-treated using the various methods are presented in Table 2. Essential amino acids (EAA) should be supplied from the diet as they cannot be synthesized in the human body; however, edible insects can be used to enhance the nutritional value of food (Kim et al, 2022a). In this study, a significant difference existed among the pre-treatment methods regarding amino acid contents.…”
Section: Amino Acid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid profiles of dried H. illucens pre-treated using the various methods are presented in Table 2. Essential amino acids (EAA) should be supplied from the diet as they cannot be synthesized in the human body; however, edible insects can be used to enhance the nutritional value of food (Kim et al, 2022a). In this study, a significant difference existed among the pre-treatment methods regarding amino acid contents.…”
Section: Amino Acid Profilementioning
confidence: 99%
“…The consumption of animal protein is increasing worldwide; however, production has lagged behind this demand ( Kim et al, 2022a ). Due to limitations in current livestock technology, the need for alternative protein sources is rising ( Ham et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Insect proteins are in the spotlight as food or feed resources (Lee et al, 2021a). Edible insect protein has high productivity and reduced carbon consumption compared to conventional livestock proteins (Kim et al, 2022a;Patel et al, 2019). Several researchers have reported that we will face drawbacks such as climate change and resource depletion, as the world population increases (Kim et al, 2021c;Nyangena et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Edible insects have been studied as protein materials in terms of future food security [ 5 , 6 ]. In particular, several studies have been conducted on materials, composed of low-molecular-weight, that can replace the traditional meat proteins [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%